On a-Kenmotsu manifolds satisfying flatness conditions - OZTURK, Hakan (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The main interest of the present paper is to study Î±-Kenmotsu manifolds that satisfy some certain tensor conditions where a is a smooth function defined by dÎ±âˆ§Î·=0 on Mâ¿. In particular, the flatness conditions of a-Kenmotsu manifolds are investigated. We conclude the paper with an example on a-Kenmotsu manifolds depending on a.